RELATIONS OF ANTHROPOLOGICAL LATENT DIMENSIONS AND SUCCES IN EXERCISES ON APPARATUSES - Dejan Madić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2010)
The sample of 260 students of the Faculty of Sport and Physical education were tested for the influence of morphological characteristics on their success in exercises on apparatuses. Negative statistically significance influence on the success in exercises on apparatuses had morphological factor of the longitudinal skeleton dimensions as well as the factor of subcutaneous tissue. There are some diferencies in results on manifest level